The value of brainstem evoked potential in clinical decision of a patient with hypoxic-ischemic encephalopathy O valor do potencial evocado auditivo em decisão clínica em paciente com síndrome hipóxico-isquêmica - Anna Lecticia R. Pinto; Franciele C.S. Costa (Arquivos de Neuro-Psiquiatria)
Establishing a prognosis for hypoxic-ischemic encephalopathy during the neonatal period is extremely difficult, as the neuroplasticity of the developing brain makes it almost impossible to measure the affected area. This case report describes a newborn with severe perinatal asphyxia and neonatal neurological syndrome including absent suck reflex. Normal brainstem auditory evoked potential led the diagnosis towards a transitory dysfunction of deglutition, and the subject received daily stimulation in the hospital environment. Suck developed satisfactorily by day of life 30 and the patient was released without having to be tube fed. Neurophysiologic tests can be of value in the clinical decisions and analysis of functional prognosis of patients with hypoxic-ischemic encephalopathy. Estabelecer o prognóstico da encefalopatia hipóxico-isquêmica durante o período neonatal é extremamente difícil, devido à neuroplasticidade do cérebro em desenvolvimento que impede a medida exata das áreas afetadas. Este relato descreve um recém-nascido a termo com grave asfixia perinatal e síndrome neurológica pós-natal, incluindo ausência do reflexo de sucção. O potencial evocado auditivo do tronco cerebral foi normal, sugerindo o diagnóstico de disfunção transitória da deglutição. Após estimulação diária no hospital a sucção foi obtida satisfatoriamente, e o paciente recebeu alta sem necessidade de alimentação enteral. Os testes neurofisiológicos podem ser de grande valor em decisões clínicas e análise funcional prognóstica de pacientes com encefalopatia hipóxico-isquêmica.